The Effect of Gamification on Purchase Decisions: Mediation of Customer Experience and Customer Brand Engagement - Barida Rakhma Nuranti; Ayu Diana Ansori; Viant Anggi Saputra; Reska Anggara Putra; Andhika Adhi Nugroho; Listya Shafa Widiyanti; Wiwit Lestari (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the effect of gamification on purchase decisions, mediated by customer experience and customer brand engagement, among users of the